2022
DOI: 10.1002/pchj.597
|View full text |Cite
|
Sign up to set email alerts
|

Temporal reproduction: A paradigm indicating a 3‐s time window

Abstract: The experimental paradigm of temporal reproduction has provided unique insights into the temporal machinery of cognitive processes. Both behavioral observations and electrophysiological methods with this paradigm indicate a time window of some 3 s.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Experiment 3 showed two clusters up to 3 s and beyond 3 s. Ample evidence has been collected about a pre-semantic time window of approximately 3 s that underlies cognitive processes as a logistic function (Bao et al, 2015;Pöppel, 1997Pöppel, , 2009Zhou et al, 2014). Using the reproduction paradigm (Mu et al, 2022), behavioral experiments with healthy adult subjects (Pöppel, 1971/72) or children (Szelag et al, 2002), with brain injured patients (Kagerer et al, 2002;von Steinbüchel et al, 1996) or autistic children (Szelag et al, 2004), and electrophysiological studies (Chen et al, 2015;Elbert et al, 1991;Wang et al, 2016) have substantiated the functionality of a time window of approximately 3 s. Thus, the data obtained in Experiment 3 support, on the one hand, the notion of this time window and, on the other hand, furthermore provide an explanation of the two clusters in serial dependence as one is dealing with two different neural processes.…”
Section: The Dependency Of Serial Dependence On Delay Timementioning
confidence: 99%
“…Experiment 3 showed two clusters up to 3 s and beyond 3 s. Ample evidence has been collected about a pre-semantic time window of approximately 3 s that underlies cognitive processes as a logistic function (Bao et al, 2015;Pöppel, 1997Pöppel, , 2009Zhou et al, 2014). Using the reproduction paradigm (Mu et al, 2022), behavioral experiments with healthy adult subjects (Pöppel, 1971/72) or children (Szelag et al, 2002), with brain injured patients (Kagerer et al, 2002;von Steinbüchel et al, 1996) or autistic children (Szelag et al, 2004), and electrophysiological studies (Chen et al, 2015;Elbert et al, 1991;Wang et al, 2016) have substantiated the functionality of a time window of approximately 3 s. Thus, the data obtained in Experiment 3 support, on the one hand, the notion of this time window and, on the other hand, furthermore provide an explanation of the two clusters in serial dependence as one is dealing with two different neural processes.…”
Section: The Dependency Of Serial Dependence On Delay Timementioning
confidence: 99%
“…Ample evidence has been collected about a pre-semantic time window of approximately 3 seconds that underlies cognitive processes as a logistic function (Bao et al, 2015; Pöppel, 1997, 2009; Zhou et al 2014). Using the reproduction paradigm (Mu et al, 2022) behavioral experiments with healthy adult subjects (Pöppel 1971/72) or children (Szelag et al, 2002), with brain injured patients (Kagerer et al, 2002; von Steinbüchel et al, 1996) or autistic children (Szelag et al, 2004), and electrophysiological studies (Chen et al, 2015; Elbert et al, 1991; Wang et al, 2016) have substantiated the functionality of a time window of approximately 3 seconds. Thus, the data obtained in experiment 3 support on the one hand the notion of this time window and on the other hand furthermore provide an explanation of the two clusters in serial dependence as one is dealing with two different neural processes.…”
Section: The Relationship Between Central Tendency and Serial Dependencementioning
confidence: 99%
“…With this perspective, time has been treated as a cognitive content, namely how we perceive durations. Various paradigms have been developed, such as duration comparison, production, estimation, and reproduction (Mu et al, 2023 ; Pöppel, 1972 ; Szelag et al, 2002 ), and many previous studies have employed these paradigms with various modifications. One study that varied the temporal structure in the reproduction paradigm revealed an intriguing finding (Pöppel, 1973 ).…”
Section: Introductionmentioning
confidence: 99%
“…At first, what attracted the most attention was the long plateau after a certain length of pause duration, which is considered to be a stable subjective perception of a duration. Such a subjective set‐point is always longer than the actual duration when the latter is shorter than about 3 s (Mu et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%